Effects of a submerged macrophyte, Ceratophyllum demersum (Ceratophyllaceae) and a cladoceran, Moina micrura (Cladocera: Moinidae) on microalgal interactions - Souza, Vitor Ricardo de; Alves Amorim, Cihelio; do Nascimento Moura, Ariadne (Revista de Biología Tropical, 2021)
Introduction: Cyanobacterial blooms in tropical water bodies are increasingly common, because of eutrophication and rising temperatures. Consequently, many freshwater systems are affected, by reducing water quality, biodiversity, and ecosystem services. With the increased frequency of harmful algal blooms, the development of biological tools to improve water quality is an urgent issue. Objective: To evaluate the effects of a submerged macrophyte and a cladoceran on the microcystin-producing cyanobacteria Microcystis aeruginosa (NPLJ-4) and the chlorophyte Raphidocelis subcapitata (BMIUFRPE-02) in mixed cultures. Methods: Two parallel experiments were carried out for ten days to evaluate the effects of the submerged macrophyte Ceratophyllum demersum and the cladoceran Moina micrura on microalgal interactions. Microalgal strains were cultivated in the ASM1 culture medium, under controlled laboratory conditions. The first experiment presented four treatments: M (C. demersum), Z (M. micrura), MZ (C. demersum and M. micrura), and C (control). Meanwhile, the second experiment consisted of five treatments, in which the microalgae were cultivated together at different Microcystis:Raphidocelis ratios: 1:0, 3:1, 1:1, 1:3, and 0:1. Biomass and growth rates of the strains were evaluated every two days, which were statistically treated with three-way or two-way repeated-measures ANOVA. Results: In the first experiment, M. aeruginosa was significantly inhibited in M and MZ treatments from the second day, and Z from the fourth, while R. subcapitata showed no reduction in its biomass in any treatment. On the other hand, R. subcapitata was stimulated from the eighth and tenth days in M treatment and only on the eighth day in Z treatment. In the second experiment, M. aeruginosa was significantly inhibited when cultivated with R. subcapitata in low ratios (Microcystis:Raphidocelis ratio of 1:3) throughout the experiment, while the chlorophyte was stimulated in that treatment. Conclusions: The coexistence of a cyanobacterium with a green alga did not alter the main negative response of M. aeruginosa to the submerged macrophyte and zooplankton but stimulated the green alga. Accordingly, the introduction of submerged macrophytes and cladocerans already adapted to eutrophic conditions, both isolated and combined, proved to be a good method to control cyanobacterial blooms without negatively affecting other coexisting phytoplankton species.